S53. Pattern of decrement in a large cohort of genetically confirmed congenital myasthenic syndromes from a single quaternary center. (May 2018) - Preethish-Kumar, Veeramani; Nalini, Atchayaram; Topf, Ana; Lochmuller, Hanns
Abstract : Introduction: Congenital myasthenic syndrome (CMS) consists of a diverse group of inherited neuromuscular junction disorders due to altered mechanisms at pre/post synaptic/synaptic cleft. Methods: Phenotypic characterization, electromyography (EMG–surface and needle) and decrement pattern using slow rate 3 Hz repetitive nerve stimulation (RNS) in facial, proximal and distal limb muscles among different subtypes of CMS. 75 cases underwent initial hot spot screening followed by targeted sequencing of known CMS genes. Results: 59 cases were genetically confirmed. Frequency: CHRNE 42(one fast channel); DOK7 8; GMPPB 4; MUSK 2; RAPSYN, AGRN, DPAGT1 one each. 16/59 had novel mutations. The common recurring mutations [CHRNE-c.1327del G; DOK7-c.1124_1127dup; GMPPB-c.1000G>A]. The mean age at onset was 4.62 ± 8.53 years (0–36). Mean age at presentation 19.09 ± 13.32 years (1–50). Mean duration to the first symptom 14.47 ± 10.79 years (1–50). M:F is 1.1:1. Consanguinity-40/59; Family history-27. Initial symptom [ptosis/opthalmoparesis-40; limb fatigue-16; other symptoms-3]. Clinically ptosis in 55/59; myopathic features-14; bulbar weakness-29. All had preserved or brisk tendon reflexes. Mean creatine kinase-382.6 ± 871.6 U/L (12–4547). Anti AchR antibodies positive in 6; Anti-MuSK antibodies in 3. Muscle biopsy done in 6/59 [2-normal; 2-subtle myopathic features; 2 GMPPB-dystrophic features]. RNS was performed in 47/59. None had double CMAP. Needle EMG- myopathic potentials in 9/59. The mean decrement ( Δ D1-4) in the muscles were: [Orbicularis oculi (36/47 cases)-22.1 ± 13.1% (Range, 15–68, no decrement (ND) in 13.8% cases); Nasalis (22/47)-22.1 ± 11.8% (Range, 13–48, ND-22%); Trapezius (31/47)-23.0 ± 12.2% (Range, 17–46, ND-16.1%); Deltoid (13/47)-33.6 ± 9.2% (Range, 21–51); Anconeus (3/47)-19.6 ± 14.1% (Range, 18–30); Abductor digiti minimi (ADM-21/47) 18.7 ± 8.5% (Range, 13–38, ND-57.2%); Abductor pollicis brevis (APB-11/47) 16.3 ± 3.5% (Range, 13–23, ND-36.3%); Quadriceps (4/47) 38.3 ± 25.3% (Range, 15–60)]. The pattern of decrement is a decrease in CMAP size within the initial 4–5 responses followed by an increment/stable CMAP with subsequent stimuli. RNS was sensitive for orbicularis oculi in all subtypes except 3 cases of CHRNE and the MUSK, AGRN cases. Nasalis was negative in 4 CHRNE cases and in AGRN. Quadriceps and deltoid were sensitive in all subtypes followed by trapezius. ADM and APB had low sensitivity except for chronic cases of CHRNE/post synaptic disorders with distal limb weakness. All responded well to pyridostigmine/salbutamol/fluoxetine. DOK7 worsened with pyridostigmine. Conclusion: This is the largest cohort of CMS from a single center reported till now with distinct clinical phenotypes. Slow rate RNS still remains as an effective, sensitive, less time consuming tool in CMS. The proximal limb muscles should be the first choice for RNS in all the genotypes followed by facial muscles. ADM/APB are less sensitive and anconeus is a better alternative.